Analisis Perkembangan Artificial Photosynthesis dengan Metode Bibliometrik Database Scopus - Eikel Kanaya; Ahmad Meiza; Mathias Nobel; Alif Safril; Nasywa Callista; Akbar Haryo Wicaksono (Universitas Proklamasi 45, 2025)
Artificial photosynthesis is one of the innovative technologies that mimics the natural photosynthesis process, aiming to convert solar energy into chemical energy that can be utilized as clean fuel. This innovative technology is regarded as a potential solution to address the energy crisis and climate change caused by high carbon dioxide (CO₂) emissions. Although artificial photosynthesis shows remarkable progress as a future energy solution, to date there has been no comprehensive bibliometric study to map the direction and potential of research in this field, hence, this study was conducted to fill the research gap. This study aims to analyze the development of research in artificial photosynthesis as a sustainable energy solution through a bibliometric approach based on the Scopus database for the period 2004–2024. The study utilized Biblioshiny and VOSviewer software, followed by analysis of publication trends, international collaborations, main keywords, institutional affiliations, as well as author impact based on the H-Index. The results of this study reveal a significant increase in the number of publications with an average annual growth of 5.37%. China, the United States, and Japan are recorded as the most active countries in publishing and collaborating research on artificial photosynthesis. This study also identifies dominant keywords and thematic trends reflecting research focuses on renewable energy, catalyst technology, and CO₂ emission reduction. The findings of this study are expected to serve as a strategic reference for the development of further research in the field of clean energy based on artificial photosynthesis.